Composite engineered biomaterial adaptable for repair and regeneration of wounds. Issue 2 (15th January 2021) - Wu, Yidi; Wagner, William D.
Abstract: Ongoing investigations in wound repair bring new opportunities and challenges for creating novel composite engineered biomaterials. Efforts have been directed toward using different combinations of biomaterials with the goal of providing an ideal biomimetic substitute for native tissue. A universal formula using collagen, fibroin and a synthetic polymer is proposed. By modifying the ratio of the building blocks, the composite material can be fabricated to match the mechanical property of different types of tissues and be further tuned to carry desirable physical and biological function. The results should provide composite engineered materials comparable to native tissue in order to repair and regenerate a variety of wounds and tissues.